Systemic treatments for radioiodine-refractory thyroid cancers - Chen, Piaohong; Yao, Yu; Tan, Huiwen; Li, Jianwei (Frontiers in Endocrinology, 2024)
Abstract： Differentiated thyroid cancers (DTCs) constitute the primary histological subtype within thyroid cancer. Due to DTCs' distinctive radioiodine (RAI) uptake mechanism, standard treatment involving surgery, with or without adjunctive therapy using RAI and levothyroxine inhibition, typically yields favorable prognoses for the majority of patients with DTCs. However, this favorable outcome does not extend to individuals with decreased RAI uptake, termed radioiodine-refractory thyroid cancers (RAI-RTCs). Recent research has revealed that the genetic mutations and gene rearrangements affecting sites such as RTKs, RAS, BRAF and TERTp lead to structural and functional abnormalities in encoded proteins. These abnormalities aberrantly activate signaling pathways like the mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-hydroxykinase (PI3K) signaling pathways, resulting in thyroid cells dedifferentiation, sodium/iodide symporter (NIS) dysfunction, and consequent the RAI-refractory nature of DTCs. Targeted therapy tailored to mutations presents a promising avenue for the treatment of RAI-RTCs. Lenvatinib and sorafenib, multikinase inhibitors, represent the standard first-line systemic treatment options, while cabozantinib is the standard second-line treatment option, for this purpose. Furthermore, ongoing clinical trials are exploring selective kinase inhibitors, immune checkpoint inhibitors, and combination therapies. Notably, numerous clinical trials have demonstrated that selective kinase inhibitors like BRAF, MEK and mTOR inhibitors can restore RAI uptake in tumor cells. However, further validation through multicenter, large-sample, double-blinded randomized controlled trials are essential,. Enhanced treatment strategies and innovative therapies are expected to benefit a broader spectrum of patients as these advancements progress.